RNA-binding proteins with basic-acidic dipeptide (BAD) domains self-assemble and aggregate in Alzheimer's disease - Bishof, Isaac (J Biol Chem, 2018)
The U1 small nuclear ribonucleoprotein 70 kDa (U1-70K) and other RNA-binding proteins (RBPs) are mislocalized to cytoplasmic neurofibrillary Tau aggregates in Alzheimer's disease (AD), yet the co-aggregation mechanisms are incompletely understood. U1-70K harbors two disordered low–complexity domains (LC1 and LC2) that are necessary for aggregation in AD brain extracts. The LC1 domain contains highly repetitive basic (Arg/Lys) and acidic (Asp/Glu) residues, referred to as a basic-acidic dipeptide (BAD) domain. We report here that this domain shares many of the properties of the Gln/Asn-rich LC domains in RBPs that also aggregate in neurodegenerative disease. These properties included self-assembly into oligomers and localization to nuclear granules. Co-immunoprecipitations of recombinant U1-70K and deletions lacking the LC domain(s) followed by quantitative proteomic analyses were used to resolve functional classes of U1-70K-interacting proteins that depend on the BAD domain for their interaction. Within this interaction network, we identified a class of RBPs with BAD domains nearly identical to that found in U1-70K. Two members of this class, LUC7L3 and RBM25, required their respective BAD domains for reciprocal interactions with U1-70K and nuclear granule localization. Strikingly, a significant proportion of RBPs with BAD domains had elevated insolubility in the AD brain proteome. Furthermore, we show that the BAD domain of U1-70K can interact with Tau from AD brains but not from other tauopathies. These findings highlight a mechanistic role for BAD domains in stabilizing RBP interactions and in potentially mediating co-aggregation with the pathological AD–specific Tau isoforms.